Isolation and Identification of Pathogenic Proteolytic Bacteria from External Body Part of GIFT Tilapia Oreochromis niloticus - D. Wahjuningrum; L. Mayasari; N.R. Mubarik (Jurnal Akuakultur Indonesia)
The aims of this research were to isolate and identify pathogenic proteolytic bacteria from external body part of GIFT tilapia and to study the role of the selected bacteria. Twenty bacterial isolates that were incubated at room temperature (25-27ºC) revealed proteolytic activity in nutrient agar containing 0.5% skimmed milk. Staphylococcus sp strain T.c2 and Necromonas sp.strain T.s2 isolates from infected tilapia  were selected based on the proteolytic index.  Postulat Koch test showed that Necromonas sp. strain T.s2. was pathogenic bacteria for tilapia and has a high value of proteolytic index.